A tyranny of petticoats : 15 stories of belles, bank robbers & other badass girls - Spotswood, Jessica; Spotswood, Jessica (Candlewick Press, 2016)
From an impressive sisterhood of YA writers comes an edge-of-your-seat anthology of historical fiction and fantasy featuring a diverse array of daring heroines.